Osteoblastoma of the rib with CT and MR imaging: a case report and literature review - Ye, Jing (BioMed Central, 2012)
Osteoblastoma is a rare bone tumor which is mostly found in the vertebral column and long bone. We describe a 59-year-old woman with osteoblastoma in the right fifth posterior segment of the rib, whose presenting symptoms were right back pain for two years and awakened at night. Chest computer tomography (CT) and thoracic spine magnetic resonance (MR) imaging findings included an expansile lesion of the right fifth rib and an ossified matrix. Surgical resection of the lesion confirmed a benign osteoblastoma. 12 months follow-up revealed disappearance of right back pain. Rib osteoblastoma in plain film has been described previously; however, to our knowledge this is the only case report emphasized in CT and MR imaging.